Redefining Mixed Reality: User-Reality-Virtuality and Virtual Heritage Perspectives - Bekele, Mafkereseb; Champion, Erik (2019)
The primary objective of this paper is to present a redefinition of Mixed Reality from a perspective emphasizing the relationship between users, virtuality and reality as a fundamental component. The redefinition is motivated by three primary reasons. Firstly, current literature in which Augmented Reality is the focus appears to approach Augmented Reality as an alternative to Mixed Reality. Secondly, Mixed Reality is often considered to encompass Augmented Reality and Virtual Reality rather than specifying it as a segment along the reality-virtuality continuum. Thirdly, most common definitions of Augmented Reality (AR), Augmented Virtuality (AV), Virtual Reality (VR) and Mixed Reality (MxR) in current literature are based on outdated display technologies, and a relationship between virtuality and reality, neglecting the importance of the users necessarily complicit sense of immersion from the relationship. The focus of existing definitions is thus currently technological, rather than experiential. We resolve this by redefining the continuum and MxR, taking into consideration the experiential symbiotic relationship and interaction between users, reality, and current virtual reality technologies. In addition, the paper will suggest some high-level overview of the redefinition’s contextual applicability to the Virtual Heritage (VH) domain.